Characteristics and Determinants of the Sublingual Microcirculation in Populations of Different Ethnicity. Issue 5 (May 2015) - Gu, Yu-Mei; Wang, Shuai; Zhang, Lu; Liu, Yan-Ping; Thijs, Lutgarde; Petit, Thibault; Zhang, Zhenyu; Wei, Fang-Fei; Kang, Yuan-Yuan; Huang, Qi-Fang; Sheng, Chang-Sheng; Struijker-Boudier, Harry A.J.; et al.
Abstract : No previous population study assessed sublingual capillary density (CD) or perfused boundary region (PBR). Lower PBR indicates greater glycocalyx width. In 252 Han and 220 She Chinese and 254 Flemish people (mean age, 51.1 years; 54.7% women), representing random population samples, we measured total and perfused CD and PBR in the sublingual capillary bed, using oblique profiled epi-illumination, and cardiovascular risk factors. In multivariable analyses, we modeled ethnicity as random effect. Significance level was α⩽0.05. Compared with Chinese, Flemish had lower total (577 versus 546 n°/mm 2 ) and perfused (338 versus 320 n°/mm 2 ) CD, but similar perfused-to-total CD ratio (mean, 0.59). Perfused-to-total CD ratio increased with age (effect size per 1–SD increase, +0.015 per year), body mass index (+0.008 per kg/m 2 ), total cholesterol (+0.012 per mmol/L), and Framingham risk score (+0.018 per point) with no ethnic differences in these associations. For age and Framingham risk score, associations with perfused-to-total CD ratio were driven by positive relationships with perfused CD, whereas associations with total CD were nonsignificant. Chinese when compared with Flemish had higher hematocrit (43.0 versus 41.1%), PBR (2010 versus 1876 nm), and pulse rate (72.6 versus 63.3 bpm). PBR standardized for hematocrit, perfused CD, and pulse rate decreased with body mass index (–26.7 nm/kg/m2), mean arterial pressure (–30.6 nm/mm Hg), and diastolic pressure (–28.5 nm/mm Hg) with no ethnic differences in these associations. In conclusion, a higher cardiovascular risk profile is associated with functional recruitment of capillaries with preserved glycocalyx that protects the endothelial lining. Abstract : Supplemental Digital Content is available in the text.